The Influence of Team Connectivity, Trust in Digital Systems, and Goal Clarity on Employee Engagement in the Digital Workplace of a Digital-Based Consulting Company - Sri Purwati; Enny Diah Astuti; Yuliani Istiqomah; Fahrina Mustafa; Muhammad Syafri (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
The research investigates how team members build their relationships with each other while their trust in digital systems and their success in reaching their work objectives impact their performance in digital consulting work environments. The research exists because organizations need to implement digital workplaces which require their employees to work at maximum capacity for their businesses to succeed. The study uses a quantitative explanatory approach with data collected through a survey of 150 employees of a digital-based consulting firm using a purposive sampling technique. The researchers conducted multiple linear regression analysis on their data after they completed all necessary work for validation purposes and reliability testing and classical assumption testing. The research found that digital workplace environments create better employee engagement when teams achieve stronger relationships with team members and their digital system trust levels and work performance capacity both improve. The study extends current research on human resource management and organizational behavior by studying digital workplace environments. The research findings deliver strategic benefits to digital-based consulting firm managers who need to create policies that enhance employee engagement while ensuring their organizations maintain sustainable operations.